2009
DOI: 10.1681/asn.2009020192
|View full text |Cite
|
Sign up to set email alerts
|

Donor Age and Renal P-Glycoprotein Expression Associate with Chronic Histological Damage in Renal Allografts

Abstract: The contributions of donor kidney quality (partially determined by donor age), allograft rejection, and calcineurin inhibitor nephrotoxicity on the progression of histologic damage of renal allografts are not completely defined. Moreover, the determinants of individual susceptibility to calcineurin inhibitor nephrotoxicity are not known but may include variability in drug transport and metabolism. In a prospective cohort of 252 adult renal allograft recipients treated with a combination of tacrolimus, mycophen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
116
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(131 citation statements)
references
References 60 publications
12
116
0
3
Order By: Relevance
“…These studies have shown evidence for an association between donor TT genotype and adverse outcome, 17,18,21 rather than CC genotype as seen in the current study. In the first study of 99 patients, donor TT genotype correlated with the development of acute cyclosporine nephrotoxicity, 17 defined on clinical grounds after a retrospective records review.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…These studies have shown evidence for an association between donor TT genotype and adverse outcome, 17,18,21 rather than CC genotype as seen in the current study. In the first study of 99 patients, donor TT genotype correlated with the development of acute cyclosporine nephrotoxicity, 17 defined on clinical grounds after a retrospective records review.…”
Section: Discussionsupporting
confidence: 66%
“…Finally, a histology-based study of the same ABCB1 SNP showed an association between donor TT genotype and the development of interstitial fibrosis and tubular atrophy on protocol biopsy specimens taken up to 3 years post-transplantation in patients treated with tacrolimus. 21 This donor genotype was not associated with other chronic histologic lesions, such as transplant glomerulopathy 22 or arterial intimal thickening. 23 The discrepancies between these 39 with the relationships denoted by D9 within the relevant box.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…86 Moreover, kidney transplant recipients who are CYP 3A5*1 expressers are more prone to develop tacrolimus-associated nephrotoxicity, especially in those who continue corticosteroid therapy. 87 Patients with hereditary nephritis may develop recurrent or de novo kidney disease after transplant.…”
Section: Recipient Factorsmentioning
confidence: 99%
“…[1][2][3]9,[51][52][53][54][55][56]59,64,71,73,76,86,[88][89][90][91][92][93] As in the recipient, old age, pre-existing hypertension, diabetes mellitus, subclinical kidney disease, and nephron under dosing (innate, female to male donor, old age, and donorrecipient body mass index mismatch) represent potential causes for development or aggravation of hypertension posttransplant. [1][2][3]9,59,64,71,73,[91][92] New evidence is emerging regarding the potential role of the donor genetic makeup in the pathogenesis of posttransplant hypertension.…”
Section: Donor Factorsmentioning
confidence: 99%